Study on the Production of Tenjo Dodol and Glutinous Rice Sweet With The Addition of Emprit Ginger - Purnawan , Lesna; Sumardi, Sumardi; Irwansyah, Novi; Adham , Ibnu; Riyanto , Slamet (The International Journal of Education Management and Sociology, 2024)
This study aims to determine (1) the optimal concentration of ginger extract for enhancing the quality of white glutinous rice dodol, and (2) the moisture content, total solids, and organoleptic evaluation of white glutinous rice dodol in accordance with the Indonesian National Standards. The research method involved mixing the water content, total solids, and organoleptic properties (color, aroma, texture, and taste) of the dodol through four treatments and three repetitions. Data were analyzed using SPSS. The treatments were as follows: 100% glutinous rice with 0% ginger extract, 95% glutinous rice with 5% ginger extract, 90% glutinous rice with 10% ginger extract, and 85% glutinous rice with 15% ginger extract. The research design used a repeated measures model with three repetitions. The highest organoleptic score for color was obtained with the addition of 10% ginger extract, receiving a score of 3.80 (liked), while the lowest score was found in the 15% ginger extract group, with a score of 3.37 (liked). For aroma, the highest score was observed in the 10% ginger extract group, while the lowest score was recorded in the 0% ginger extract group. Texture received the highest score in the 0% ginger extract group. The taste evaluation revealed that the highest score, 4.47 (liked), was in the 10% ginger extract group, and the lowest score was found in the 0% ginger extract group. The analysis of variance results indicated that there was no significant difference among the treatments (p > 0.05), and no further testing was necessary.